The synthesis, carbonic anhydrase and acetylcholinesterase inhibition effects of sulfonyl chloride moiety containing oxazolidinones using an intramolecular aza-Michael addition - Yildirim, Alper; Atmaca, Ufuk; Sahin, Ertan; Taslimi, Parham; Taskin-Tok, Tugba; Celik, Murat; Gülçin, İlhami; Taslimi, Parham (Taylor & Francis Inc, 2025)
Oxazolidinones are used as various potent antibiotics, in organisms it acts as a protein synthesis inhibitor, focusing on an initial stage that encompasses the tRNA binding process. Novel intramolecular aza-Michael reactions devoid of metal catalysts have been introduced in an oxazolidone synthesis pathway, different from alpha,beta-unsaturated ketones. Oxazolidinone derivatives were tested against acetylcholinesterase (AChE), carbonic anhydrase I and II (hCA I and hCA II) enzymes. All the synthesized compounds had potent inhibition effects with Ki values in the range of 13.57 +/- 0.98 - 53.60 +/- 6.81 mu M against hCA I and 9.96 +/- 1.02 - 46.35 +/- 3.83 mu M against hCA II in comparison to the acetazolamide (AZA) (Ki = 50.46 +/- 6.17 mu M for hCA I) and for hCA II (Ki = 41.31 +/- 5.05 mu M). Also, most of the compounds demonstrated potent inhibition ability towards AChE enzyme with Ki values 78.67-231.75 nM and compared to tacrine (TAC) as standard clinical inhibitor (Ki = 142.48 nM). Furthermore, ADMET analysis and molecular docking were calculated using the AChE, hCA I and hCA II enzyme proteins to correlate the data with the experimental data. In this work, recent applications of a stereoselective aza-Michael reaction as an efficient tool for of nitrogen-containing heterocyclic scaffolds and their useful to pharmacology analogs are reviewed and summarized.Communicated by Ramaswamy H. Sarma
Keywords: Oxazolidinone; Aza-Michael Addition; Antibiotics; Bioactivity; Molecular Docking; Admet